Percepção de privacidade em redes sociais - Gustavo Costa Rauber (2012)
Online social networks such as Facebook, Twitter and LinkedIn have experienced exponential growth in recent years. Users are spending more time on Online Social Networking (OSN) sites than on any other sites and services on the Internet. Users post and share a lot of personal information on these sites without being aware of their privacy implications. Personal information posted on these OSNs can be a treasure for marketing companies and cyber criminals. Characterizing the privacy awareness of users is important to design technologies and policy solutions. Users expect the OSN site to provide good privacy protection or provide controls so they can make informed decisions about their privacy. This dissertation investigates the privacy awareness ofusers on Facebook, the largest OSN. The present study is one of the first to characterize the privacy awareness on OSN through a real world experiment, not self-reported data. The main findings are: only a low percentage of users change the default privacy settings; most users expose their gender and friends list publicly; most users who havecommend their location information to Facebook expose it publicly; users exercise morecontrol over content with more potential to endanger their reputation; people tagged by an individual form strong-tie egocentric networks; an important share of users expose their full date of birth to their network; the aggregation of individual bits can revealonce private information.